2019
DOI: 10.18332/tpc/114229
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking, ENDS use and dual use among a national sample of lesbians, gays and bisexuals

Abstract: INTRODUCTION Historically, lesbian, gay and bisexual (LGB) individuals have higher rates of cigarette smoking, often attributed to targeted tobacco advertising, exposure to stressors, and psychological distress. Elevated use of electronic nicotine delivery systems (ENDS) among LGB individuals has been documented recently. However, the LGB groups are not homogeneous and differences may exist between the use of tobacco by men and women within the LGB groups. The purpose of this research was to examine cigarette … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Previous studies have found higher tobacco use rates in youth who identify as bisexual 8,14 , including increased risk in adolescent bisexual girls 7,12,14 and lesbians 7,12 , pointing to increased risk for usage and ultimately adverse health outcomes for sexual minority girls 15 . Although studies with youth sexual minority subpopulations are few, research with adults has reported that lesbians and bisexual women have greater odds of tobacco use 16 , including dual use 17 , with some research suggesting that bisexual women are particularly at risk 18,19 . However, this study is one of the first to report significantly greater odds of dual/poly tobacco use by female sexual minority youth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found higher tobacco use rates in youth who identify as bisexual 8,14 , including increased risk in adolescent bisexual girls 7,12,14 and lesbians 7,12 , pointing to increased risk for usage and ultimately adverse health outcomes for sexual minority girls 15 . Although studies with youth sexual minority subpopulations are few, research with adults has reported that lesbians and bisexual women have greater odds of tobacco use 16 , including dual use 17 , with some research suggesting that bisexual women are particularly at risk 18,19 . However, this study is one of the first to report significantly greater odds of dual/poly tobacco use by female sexual minority youth.…”
Section: Discussionmentioning
confidence: 99%
“…Lesbian and bisexual women (LBW) have a higher prevalence of tobacco use than heterosexual women ( Li et al, 2021 , Wheldon et al, 2018 , Ridner et al, 2019 ) (e.g., 37.7% for bisexual, 31.7% for lesbian, and 16.6% for heterosexual women ( Li et al, 2021 )). One reason for tobacco use inequities is targeted marketing of tobacco products to the lesbian, gay, bisexual, and transgender (LGBT) community ( Emory et al, 2019 , Tan et al, 2021 , Dilley et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…LBW are not a monolith, and disparities in tobacco use and advertisement exposures exist within this group. Bisexual women, in particular, have the highest prevalence of tobacco use among all women ( Li et al, 2021 , Ridner et al, 2019 , Johnson et al, 2016 , McCabe et al, 2018 , Emory et al, 2016 ), and they report greater exposure to tobacco advertisements than lesbian (and heterosexual) women ( Tan et al, 2021 ). Additionally, the distribution of tobacco use according to race and ethnicity differs for LBW vs. heterosexual women.…”
Section: Introductionmentioning
confidence: 99%